Corporate management: Strategies and practices for business success corporate - Pontes, Cláudio Marinho de Pinho; Dusek, Patricia Maria (Seven Editora, 2023)
This article explores the field of corporate management, addressing strategies and practices that can lead to business success. Corporate management is critical to ensuring an organization’s operational efficiency, financial sustainability, and growth. In this article, we will discuss the key areas of focus in corporate management, such as leadership, governance, human resource management, business strategy, and corporate social responsibility. In addition, case studies and practical examples will be presented to illustrate the application of these strategies in the real world. By the end of the article, it is hoped that readers will have gained a deeper understanding of the importance of corporate management and will be able to implement effective practices in their organizations. DOI:https://doi.org/10.56238/sevened2023.006-017